Tipe Kepemimpinan Profetik Konsep dan Implementasinya dalam Kepemimpinan di Perpustakaan - Ahmad Anwar (IAIN Ponorogo, 2017)
The study of Ideal leadership concept currently still becomes an interesting topic. From Islamic perspective, the nature of human being who descended to earth is to be a leader. Furthermore, during the leadership history, Prophet Muhammad is named as an ideal leader due to his success of gaining many followers in the religious proselytizing. The leadership model that is conducted by the prophet is known as prophetic leadership. During his time of being a prophetic leader, he is also included in the situational leadership theory, in which the theory is the combination of authoritarian, laissez faire, and democratic leadership. This kind of leadership model is very suitable to be applied in anywhere. In this study, the writer explains about situational leadership that has been applied by Prophet Muhammad in a micro organization called library. This study is significance as an alternative leadership model that can be applied by the head of library